Contextualizing Arab female entrepreneurship in the United Arab Emirates. Issue 5 (20th October 2019) - Erogul, Murat Sakir; Rod, Michel; Barragan, Salvador
ABSTRACT: Cultural and structural challenges within the Arab context are found to constrain women's opportunities towards entrepreneurial development and activity. In addressing the call for feminist theorizing in entrepreneurship research, we bring together gender, identity and networking into the subjective experiences of Emirati female entrepreneurs. Through antenarrative perspectives, we demonstrate that developing cooperation with men is a viable and complementary means to addressing contextual challenges and achieving empowerment. Our contribution illustrates that Emirati female entrepreneurs' multi-layered identity work manifests in a relational manner via efforts to strategically construct opportunity by means of engaging in discursive relationships with men.